2021
DOI: 10.1017/pds.2021.526
|View full text |Cite
|
Sign up to set email alerts
|

Shifting From Blended to Online Learning: Students’ and Teachers’ Perspectives

Abstract: The Covid-19 outbreak forced many universities across the world to transition from a traditional or blended format to fully online education. This paper presents a case study on the transition to an online education format for a circular design course. Both quantitative and qualitative data were collected through a survey with 26 students and interviews with six course teachers. The findings revealed that students preferred the on-campus versions over the online course components. They indicated the perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…One of the greatest opportunities comes from the development of the concept of universal access to education throughout life [10]. While technological advances in education have made life easier for students [11], at the same time, studies showed that students prefer hybrid courses compared with those offered entirely online [11,12]. Therefore, by analyzing data and results collected from various research papers, we can identify and evaluate specific behaviors, as well as discover problems related to specific communication styles and new interaction patterns among participants.…”
Section: New Learners' Interaction Patternsmentioning
confidence: 99%
“…One of the greatest opportunities comes from the development of the concept of universal access to education throughout life [10]. While technological advances in education have made life easier for students [11], at the same time, studies showed that students prefer hybrid courses compared with those offered entirely online [11,12]. Therefore, by analyzing data and results collected from various research papers, we can identify and evaluate specific behaviors, as well as discover problems related to specific communication styles and new interaction patterns among participants.…”
Section: New Learners' Interaction Patternsmentioning
confidence: 99%
“…For interpreting courses, the common denominators of the two modes of learning include traineecenteredness, cultivation of interpreter competence, and course design based on real-life features of interpreting, contents delivery and stringent tests, while the differences lie in assignments, application of ICTs for classes and tests [11]. Furthermore, Polat et al have compared those two modes for the circular design course, revealing that students prefer the on-campus versions over the online course components because the latter are perceived as a mode that lacks motivation and a sense of community but imposes a high workload on the students, while teachers identify the virtual mode as an advantage to their teaching and student's learning experiences despite a lack of teacher-student connection [12].…”
Section: Literature Reviewmentioning
confidence: 99%